Gondwana accretion tectonics and implications for the geodynamic evolution of eastern Arabia: First structural evidence of the existence of the Cadomian Orogen in Oman (Jabal Akhdar Dome, Central Oman Mountains). (January 2020) - Callegari, Ivan; Scharf, Andreas; Mattern, Frank; Bauer, Wilfried; Pinto, Andre Jorge; Rarivoarison, Heninjara; Scharf, Katharina; Al Kindi, Mohammed
Highlights: Two early Cambrian compressive events are recorded in the Jabal Akhdar Dome. Shortening axis of the earlier and later events are NE-SW and NW-SE, respectively. The earlier and later events are related to the Cadomian and Angudan orogenies. Abstract: This work describes two early Cambrian folding events within Cryogenian to earliest Cambrian rocks of the western Jabal Akhdar Dome (NE Oman). This sequence is truncated at an angular unconformity and overlain by a Permo-Mesozoic succession that is folded into a wide, gentle anticline, that differs in style and intensity of deformation from that below the unconformity. An older Paleozoic deformation (D1) have been identified within limestone of the Hajir Formation, in which F1 metric folds reflect ductile deformation affecting Neoproterozoic-Cambrian rocks with low dip-angle axial planes. A younger event (D2) has refolded the F1 folds with open to close F2 folds with sub-vertical to steep axial planes dipping towards NNW and fold axes plunging either ENE-wards with 50°, or SW-wards with 30°, at the northern and southern flanks of the Jabal Akhdar Dome, respectively. The F2 folds have been discussed by previous authors as possibly Hercynian in age, while the F1 folds are here firstly presented, revealing a uniform NE-vergence of F1 folds after restoration at pre-D2 geodynamic conditions. First structural evidence of a tectonic event in eastern Arabia dates between 542 and 525 ± 5 Ma (D1), due to the convergence between Arabia and microcontinents and/or oceanic subduction of the Proto-Tethys Ocean. D1 and D2 are related to NE-SW and NW-SE main compressional directions, respectively. Based on geometric and time considerations D1 correlates with the Cadomian and D2 with the Angudan orogenies. Our evidences directly question former discussions of the presence of the "Hercynian Orogen" in eastern Arabia.